26. THE OCCURRENCE OF AFLATOXIN B1 CONTAMINATION IN RICE AND RICE PRODUCT IN CAN THO, 2024 (Vietnam Journal of Community Medicine, 2025)
Objectives: Description of Aflatoxin B1 contamination in rice and rice products, samples collected at traditional markets in Can Tho city, December 2024.Method: A total of 130 rice samples were analyzed for Aflatoxin B1 quantification. Mycotoxin analysis was performed by high-performance liquid chromatography using fluorescence detection. Test results are evaluated according to QCVN No.8-1:2011/BYT.Results: The average concentration of Aflatoxin B1 in processed rice was 1.28 µg/kg; processed rice products were 1.27 µg/kg; and rice that had to be pre-processed before use was 4.27 µg/kg. The results showed that 78.5% of the samples were contaminated with mycotoxins and 15.4% of the samples exceeded the allowable standard.Conclution: 15.4% of rice and rice product samples taken from traditional markets in Can Tho city in 2024 had Aflatoxin B1 concentrations were exceeded the allowable standard.
Keywords: Aflatoxin B1; gạo và sản phẩm từ gạo; Cần Thơ